Self-Determination and Conformity with Student Career Decision Making, How Are They Related? - Rahmasari, Yunita; Noviekayati, IGAA; Pratitis, Niken Titi (IJOSMAS, 2023)
Every student must have aspirations to be able to continue their education at the tertiary level, but there are some students who are still confused about choosing a college major. The purpose of this study was to analyze the relationship between self-determination and conformity with students' career decision making. This study uses quantitative research methods with data collection in the form of a psychological scale. The subjects of this study were 200 students of Bumi Shalawat Sidoarjo Progressive High School. The analytical method uses multiple regression analysis assisted by SPSS version 20 for windows . Based on the results of data analysis, the results of the first and second hypotheses are accepted, so it can be concluded that self-determination and conformity are correlated with student career decision making simultaneously. Self-determination has a positive correlation with student career decision making partially but conformity with student career decision making has a negative correlation that is not significant.